2008
DOI: 10.1007/s11334-008-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

Formal models for user interface design artefacts

Abstract: There are many different ways of building software applications and of tackling the problems of understanding the system to be built, designing that system and finally implementing the design. One approach is to use formal methods, which we can generalise as meaning we follow a process which uses some formal language to specify the behaviour of the intended system, techniques such as theorem proving or model-checking to ensure the specification is valid (i.e., meets the requirements and has been shown, perhaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…For example, Duke et al (1999) showed that formal specification techniques based on set theory can clarify what information can or should be presented to users and to specify the effect user actions should have. Bowen and Reeves (2008) proposed to formalize the meaning of user-centered design outcomes in a presentation model based on set theory. This approach ensures correct and robust implementation of design guidelines describing UI properties or design rules, such as rules for consistency.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Duke et al (1999) showed that formal specification techniques based on set theory can clarify what information can or should be presented to users and to specify the effect user actions should have. Bowen and Reeves (2008) proposed to formalize the meaning of user-centered design outcomes in a presentation model based on set theory. This approach ensures correct and robust implementation of design guidelines describing UI properties or design rules, such as rules for consistency.…”
Section: Discussionmentioning
confidence: 99%
“…The first are the sets of properties of the interactive systems and devices which are known to exist in a given location. For our previous work with safety critical medical devices we typically already had initial models (based on the presentation models of (Bowen and Reeves, 2008)) from which we could automatically extract widget and interaction information. As the interactive systems we are now dealing with are not safety critical, this is less likely to be the case and so we manually create the sets of properties of interest.…”
Section: Models and Reasoningmentioning
confidence: 99%
“…We create a link between the formal specification of the system and the user interface design by creating presentation models and presentation and interaction models (PIMs) [BR06], BR08a]. The presentation model gives a description of the interface designs based on the interactive elements (widgets) of the design.…”
Section: Example Systemmentioning
confidence: 99%
“…The combination of the system specification and the UI models (presentation models, PIM and PMR) provides a formal description of the entire system. We have previously shown how we can use this information as a way of ensuring correctness of the the proposed system [BR08a] and also as the basis for refinement [BR08b]. In this paper, however, we will use the models to derive tests which can then be run on an implementation of the system.…”
Section: Example Systemmentioning
confidence: 99%
See 1 more Smart Citation